PENGARUH KOMUNIKASI ENDORSER PADA MEDIA INSTAGRAM TERHADAP BRAND AWARENESS - Anggraeni, Intan; Putri, K. Y.S. (Jurnal Common, 2022)
Nowadays, the development of technology is increasingly advanced, many business people use digital platforms as marketing strategy tools. The unlimited flow of information about space and time has an impact both positively and negatively. The emergence of internet technology that is growing rapidly affects the use of social media among the public. Social media is a real form of technological advancement from the development of new media. Social media is an online based media that allows to interact with each other. One stage of marketing products by growing brand awareness for consumers Brand awareness is the ability of consumers or prospective consumers in remembering a brand. One way he does it is endorsment. The current endorsment phenomenon on social media is a development of marketing communication. Endoser usually comes from celebrities or famous figures who have fame in society, this is what businesses use in attracting consumers. The purpose of this study was to find out the Influence of Endoser Communication on Instagram media on Brand Awareness. Research methods used quantitatively. Samples used as many as 45 respondents. From the calculation results using SPSS 22 known correlation coefficient value (r) of 0.418 which means that the level of relationship between endoser communication and brand awareness is moderate and positive. The results showed that there is a significant influence between edoser communication on brand awareness, this is evidenced by the significance value of 0.004 < 0.05 and the known t test t calculated 3,030 > t table 2.016 and the influence of endoser communication on buying interest is 0.175 which means the amount of independent variable influence in influencing dependent variables is 17.5% while the remaining 82.5% is influenced by other variables.